Child Protection In Marriage Dispensation: Harmonization of Regulations From The Perspective of The Child Protection Law - Aura Shava Dhinda Salsabila; Rachmi Sulistyarini; Djumikasih (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
Child marriage remains a legal and social issue in Indonesia despite the existence of regulations regarding child protection in the national legal system. Law Number 35 of 2014 concerning Child Protection expressly requires parents to prevent child marriage as a form of protection for children's rights to growth and development. However, on the other hand, Law Number 16 of 2019 concerning Marriage still provides space through the marriage dispensation mechanism that can legalize child marriage through a court decision. This condition creates disharmony in regulations and impacts legal uncertainty in child protection. This study aims to analyze the harmonization of marriage dispensation regulations from the perspective of the Child Protection Law and examine legal certainty regarding child protection in the practice of marriage dispensation in Indonesia. This study uses a normative legal research method with a conceptual approach and a case approach. The legal materials used include laws and regulations, court decisions, scientific journals, and legal literature analyzed using grammatical and systematic interpretation methods. The research results indicate that there is a dualism in the regulations between the Child Protection Law and the Marriage Law, resulting in weak legal protection for children. Furthermore, the ambiguity of the phrase "very urgent reasons" in the marriage dispensation creates multiple interpretations and high levels of judicial discretion in granting marriage dispensation requests. Therefore, regulatory harmonization, strict limitations on marriage dispensations, and strengthening of the child protection paradigm in judicial practice are needed to achieve legal certainty oriented toward the best interests of children.